Trends in Nutritional Status among Children under Five in Nepal : Findings from the Nationally Representative Surveys 1996-2022 - Manandhar, Raju; Acharya, Pitambar; Acharya, Devaraj; Thasineku, Om Chandra; Paudel, Netra Raj; Dhakal, Ram Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Malnutrition among children which includes stunting, wasting, and underweight remains a serious public health concern in Nepal. It exists despite tremendous progress since 1996, especially for children from the poorest households, those born to mothers with lower levels of education, and those living in rural areas. To achieve SDG 2.2, which calls for the eradication of all forms of malnutrition by 2030, it is crucial to understand trends and disparities in nutritional status to guide targeted interventions. The study examines trends in stunting, wasting, and underweight among children under five years old, using data from the Nepal Demographic and Health Surveys (NDHS) and other national surveys. The analysis focuses on variations by residence (urban/rural), gender, mother’s education level, child’s age, and household wealth quintile. Child malnutrition has been found to have significantly declined, as per analysis of NDHS data for the period 1996 to 2022. The rate of underweight decreased from 42.3% to 18.7%, wasting decreased from 14.8% to 7.7%, and stunting decreased from 56.6% to 24.8%. However, the prevalence of malnutrition is found to be higher among the children from the lowest wealth quintile, children of uneducated mothers, in rural areas. Also, there is some level of gender variations in malnutrition, which peaks between the ages of 18 and 35 months. Despite the substantial nationwide improvements in child nutrition from 1996 to 2022, inequalities persist in terms of rural-urban residence, mothers' education, wealth quintile, and the period of 18–35 months as a vulnerable period. It demands targeted, equity-focused interventions to sustain progress and achieve national and global nutrition targets